One Belt One Road and Global Maritime Fulcrum: Between Contradictions and Harmony - Catharina Dheani (Jurnal Sentris, 2017)
A story of connectivity, part of the international diplomatic arena with routes, hubs, and corridors has been set as the mantra of the Belt and the Road of China. In 2013, when China’s paramount leader, Mr. Xi took a visit in mostly Central Asia and Southeast Asia, he initiatively proposed to build the Silk Road Economic Belt and the 21st Century Maritime Silk Road. It is then being abbreviated as OBOR (One Belt One Road) which represents China’s audacious vision to transform political region in Europe, Africa, and Asia for decades to come. The initiative absolutely calls for a greater integration of those regions into a cohesive economic area through building infrastructure, increasing cultural exchanges, and broadening trade. This centerpiece of Mr. Xi’s foreign policy has been categorized as the most important feature of the country to show its charm in offering a deeper connection and a bundle of developmental pledges towards all neighboring countries. Indonesia, the south neighboring country of China, is also included in the orbit of convergence with Jokowi’s vision and foreign politics strategies ‘to be a global maritime fulcrum.’ Both are in attempt to reinvigorate what each apprehends as their previous maritime glory. However, there are several limits of cooperation between the two sides, in particular the territorial issue in the South China Sea. Confrontations in fishing and coast guard ships, including a domineering manner of China’s foreign conduct are the current impediments to advance cooperation. Yet, it is evident that Indonesia will need Chinese investments in order to realize the Global Maritime Fulcrum. All in all, this research aims to analyze the concept of connectivity between two sides as well as to explore on how Indonesia and China could maintain their partnership to achieve each specific national goals without stepping on each other’s toes